2020
DOI: 10.1007/s00025-020-1164-y
|View full text |Cite
|
Sign up to set email alerts
|

Convolution Systems on Discrete Abelian Groups as a Unifying Strategy in Sampling Theory

Abstract: A regular sampling theory in a multiply generated unitary invariant subspace of a separable Hilbert space H is proposed. This subspace is associated to a unitary representation of a countable discrete abelian group G on H. The samples are defined by means of a filtering process which generalizes the usual sampling settings. The multiply generated setting allows to consider some examples where the group G is non-abelian as, for instance, crystallographic groups. Finally, it is worth to mention that classical av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…where λ min (respectively, λ max ) denotes the smallest (respectively, the largest) eigenvalue of the positive semidefinite matrix A(ξ) * A(ξ) (see Ref. [15]).…”
Section: First Of All the Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…where λ min (respectively, λ max ) denotes the smallest (respectively, the largest) eigenvalue of the positive semidefinite matrix A(ξ) * A(ξ) (see Ref. [15]).…”
Section: First Of All the Mappingmentioning
confidence: 99%
“…To be precise, the samples used along this paper will be expressed as the output of a discrete convolution system in the product Hilbert space ℓ 2 N (Λ) := ℓ 2 (Λ)ו • •×ℓ 2 (Λ) (N times), and then it will be used the close relationship between discrete convolution systems and sequences of translates in ℓ 2 N (Λ) (see, for instance, Ref. [15]). The other involved tools are the Kohn-Nirenberg transform or the Weyl transform for Hilbert-Schmidt operators: both are unitary operators from L 2 (R 2d ) onto HS(R d ) which respect the translations in the sense that, if we denote any of them by L, we have L(T z f ) = α z (Lf ) for f ∈ L 2 (R 2d ) and z ∈ R 2d .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The used mathematical techniques are similar to those in Ref. [14]. They lie in exploiting the relationship between discrete convolution systems and frames of translates in the product Hilbert space ℓ 2 N (H) := ℓ 2 (H) × • • • × ℓ 2 (H) (N times); this is an auxiliary space isomorphic to H U,φ,Φ .…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The second part of this article, shows that by means of these convolution operators, an interesting generalization of some relevant results about shift-invariant systems can be obtained. In reference [11], it is showed that they are also useful in order to obtain a regular sampling theory in a very general context.…”
Section: Introductionmentioning
confidence: 99%